Assessing body awareness and autonomic reactivity: Factor structure and psychometric properties of the Body Perception Questionnaire‐Short Form (BPQ‐SF). Issue 2 (28th November 2017) - Cabrera, Ana; Kolacz, Jacek; Pailhez, Guillem; Bulbena‐Cabre, Andrea; Bulbena, Antonio; Porges, Stephen W.
Abstract: Body awareness and reactivity dysfunction are characteristic of a range of psychiatric disorders. Although the neural pathways communicating between the body and brain that contribute to these experiences involve the autonomic nervous system, few research tools for studying subjective bodily experiences have been informed by these neural circuits. This paper describes the factor structure, reliability, and convergent validity of the Body Awareness and Autonomic Reactivity subscales of the Body Perception Questionnaire‐Short Form (BPQ‐SF). Exploratory and confirmatory factor analyses were applied to data from three samples collected via the internet in Spain and the US and a college population in the US (combined n  = 1320). Body awareness was described by a single factor. Autonomic reactivity reflected unique factors for organs above and below the diaphragm. Subscales showed strong reliability; converged with validation measures; and differed by age, sex, medication use, and self‐reported psychiatric disorder. Post hoc analyses were used to create the 12‐item Body Awareness Very Short Form. Results are discussed in relation to the distinct functions of supra‐ and sub‐diaphragmatic autonomic pathways as proposed by the Polyvagal Theory and their potential dysfunction in psychiatric disorders.